XaaS everything-as-a service : the lean and agile approach to business growth - Bhattacharya, Shantanu; Bhattacharya, Lipika (World Scientific, 2022)
"XaaS: Everything-as-a-Service: The Lean and Agile Approach to Business Growth takes the reader into the bold new world of pay-per-use for a product or service. From the perspective of the customer, the servitization model yields multiple benefits: the consumer can try out the product/service at a relatively low cost, the risk is mitigated, capital expenses can be converted into operating expenses, it is not needed to forecast how often the product/service is used, and only parts of the product/service needed can be used. Similarly, a provider can benefit by having a larger market coverage, steadier stream of revenues, upgrades as and when needed, sharing of fixed assets across consumers, practicing of value-based pricing, and unbundling or bundling utility for consumers using appropriate pricing techniques. However, this "nanoization" of products/services is tricky, and has to be designed carefully. This book provides a set of recipes to providers to adopt the XaaS model by changing the provider's mindset: dividing the product/service forces the provider to take a value-driven approach to his product/service, and consequently, eliminate all non-value added activities. The requirements of the XaaS model serve both as an objective to the innovation and internal processes of the provider, and as guide to understanding the customer's needs. The book also covers data acquisition, data analysis and synthesis, and data application needs of the XaaS model, with simple examples and case studies from the business world of firms that achieve these objectives successfully"--
Keywords: Business planning; Verbundangebot; Systemgeschäft; Unternehmenswachstum; Hybrides Leistungsbündel; Electronic books